Northern Shrimp (Pandalus borealis) on Flemish Cap Surveys 2018 - Casas-Sánchez, José Miguel (2018)
A stratified random bottom trawl survey on Flemish Cap was carried out from June 25th to July 25th 2018. The area surveyed was extended up to depths of 800 fathoms (1450 meters) following the same procedures as in previous years. This year a total of 181 valid hauls were made by the vessel R/V Vizconde de Eza with the usual survey gear (Lofoten), 120 up to 730 meters depth. The surveyed area has properly prospected the 32 strata planned. The general indexes for shrimp were estimated taken into account the traditional swept area (strata 1-19, up to depths of 730 m.) and the total area surveyed (strata 1-34, up to depths of 1450 m.). As the last years the strata 26 and 27sited in the southeast of the bank with depths from 600 to 800 fathoms (1100- 1400 m.) will not be surveyed due to the presence in the bottoms of great quantities of mud and sponges. The results concerning shrimp are presented and compared to those from previous years of the same series. In recent years 2015, 2016, 2017 and 2018 the total biomass indexes increased significantly compared to previous year (around 72%, 62%, 14% and 52 % respectively) but remain below average. The total and female biomasses estimated in 2018 were 4394 t and 4051 t respectively (Table 1). As in previous years the youngest specimens (age 1, around 10 mm CL) barely appeared in the catches and the abundance at age 2 (around 16 mm CL) increased at levels next to reported in 2009 and 2010 but remains at low level and suggesting the absence of any strong year classes since 2004. Although the new information indicates a slight improvement and the stock is now outside the collapse zone, it remains in a state of impaired recruitment that confirms the recommendation carried out within Scientific Council during autumn 2017. Sí